Counseling Students’ Experiences in an Islamic-Based Counseling Course - Sumari, Melati; Dini Farhana Baharudin (Springer New York LLC, 2024)
The purpose of this study was to examine the experiences of learning and consequent development of twelve students enrolled in a four-year undergraduate counselling program at a higher institution of learning in Malaysia. The students’ ages ranged from 20 to 24 years. Participants outlined their learning experiences after taking a three-credit semester-long course on Islamic-based counseling, which was an attempt at integrating religion and spirituality into counselor training. An experiential learning theory served as the framework of reference, and a qualitative research design was adopted. Results revealed four major themes: (1) increased understanding of counseling, (2) better understanding in regard to the self and relationship with God, (3) applicability to daily practice, and (4) enhancing professional competence as a counselor. Finally, implications for research, counselor education and training, and clinical practice are discussed.